Excellent low-voltage operating flexible ferroelectric organic transistor nonvolatile memory with a sandwiching ultrathin ferroelectric film - Ting Xu (Nature Portfolio, 2017)
Abstract The high operating voltage is a primary issue preventing the commercial application of the ferroelectric organic field-effect transistor (Fe-OFET) nonvolatile memory (NVM). In this work, we propose a novel route to resolve this issue by employing two ultrathin AlOX interfacial layers sandwiching an ultrathin ferroelectric polymer film with a low coercive field, in the fabricated flexible Fe-OFET NVM. The operation voltage of Fe-OFET NVMs decreases with the downscaling thickness of the ferroelectric film. By inserting two ultrathin AlOX interfacial layers at both sides of the ultrathin ferroelectric film, not only the gate leakage is prominently depressed but also the mobility is greatly improved. Excellent memory performances, with large mobility of 1.7 ~ 3.3 cm2 V−1 s−1, high reliable memory switching endurance over 2700 cycles, high stable data storage retention capability over 8 × 104 s with memory on-off ratio larger than 102, are achieved at the low operating voltage of 4 V, which is the lowest value reported to data for all Fe-OFET NVMs. Simultaneously, outstanding mechanical fatigue property with the memory performances maintaining well over 7500 bending cycles at a bending radius of 5.5 mm is also achieved in our flexible FE-OFET NVM.